Spiderwick Chronicles: A Giant Problem - Book 7 - DiTerlizzi, Tony; Black, Holly (New York : Simon & Schuster Books for Young Readers, 2023)
As giants start waking up and destroying everything around their Florida neighborhood, Nick, Laurie, Jules, and Cindy work frantically to find a solution.
Keywords: Giants (Folklore) -- Juvenile fiction; Goblins -- Juvenile fiction; Siblings -- Juvenile fiction; Magic -- Juvenile fiction; Giants -- Fiction; Goblins -- Fiction; Brothers and sisters -- Fiction; Magic -- Fiction; Florida -- Juvenile fiction; Florida -- Fiction; Fantasy fiction